The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1021/ic034373n
|View full text |Cite
|
Sign up to set email alerts
|

Structural Study on Highly Oxidized States of a Water Oxidation Complex [RuIII(bpy)2(H2O)]2(μ-O)4+ by Ruthenium K-Edge X-ray Absorption Fine Structure Spectroscopy

Abstract: The oxidation-induced structural change of a water-oxidizing diruthenium complex, [(bpy)(2)(H(2)O)Ru(III)(micro-O)Ru(III)(OH(2))(bpy)(2)](4+) (bpy = 2,2'-bipyridine), was investigated by means of X-ray absorption spectroscopy. Ru K-edge XANES (X-ray absorption near-edge structure) spectra from the acidic solution and solid precipitates obtained by oxidation showed that the absorption edge shifts toward higher energy with a preedge feature slightly more enhanced than those of the lower oxidation states. This in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 35 publications
5
26
0
Order By: Relevance
“…X-ray structures of these complexes are available 3,10 and the K-edge EXAFS was previously reported. 31 Ru K-edge XANES of the blue dimer [3,3] and [3,4] have been reported 31 but assignment of Ru oxidation states was not validated by comparison with model compounds. Figure 1 shows XANES spectra of the blue dimer [3,3] and [3,4] as well as spectra of a related Ru(II) complex and ruthenium(IV) oxide (RuO 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…X-ray structures of these complexes are available 3,10 and the K-edge EXAFS was previously reported. 31 Ru K-edge XANES of the blue dimer [3,3] and [3,4] have been reported 31 but assignment of Ru oxidation states was not validated by comparison with model compounds. Figure 1 shows XANES spectra of the blue dimer [3,3] and [3,4] as well as spectra of a related Ru(II) complex and ruthenium(IV) oxide (RuO 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Meyer et al reported (1) in the early 1980's as a water-oxidation catalyst capable of a moderate number of turnovers ( Table 1). Since that time, 1 has become one of the most studied water oxidation catalysts [53][54][55][56][57]. Even with 25 years of study, the mechanism by which 1 oxidizes water is still under active discussion [58][59][60][61][62].…”
Section: Functional Modelsmentioning
confidence: 99%
“…The green solid 5b was collected in 55% yield (0.0564 g, 0.0638 mmol). 1 H NMR (CD 2 Cl 2 ): δ 19.07 (s, 1H, CHPh), 25 8. 65 (br.…”
Section: Synthesismentioning
confidence: 99%
“…However, the prevalence of heavier transition metals in biological and homogeneous catalysis suggests that similar information would be of great utility beyond the first-row transition metals. It has generally been assumed that the pre-edge features for second-row transition metals are due to 4d←1s transitions by analogy to first-row metals; although, in many cases, the possibility of 5p←1s transitions has not been excluded [5][6][7][8]. More detailed studies of Mo [9] and Pd [10] K-edges have provided reasonable assignment of pre-edge features for these metals as due to metal 4d←1s transitions.…”
Section: Introductionmentioning
confidence: 99%